"Should have I Bought the other One?" Experiencing Regret in Global versus Local Brand Purchase Decisions. Issue 2 (June 2018) - Davvetas, Vasileios; Diamantopoulos, Adamantios
This research addresses the unexplored postpurchase dynamics of global/local brand choices by investigating the experience of regret in global versus local brand purchases. Drawing on regret theory, the authors demonstrate in four complementary studies that the global/local availability of both chosen and forgone brands influences consumer responses to regrettable purchases and that the direction and magnitude of this influence depend on the consumers' product category schema and global identity. Study 1 shows that regrettable decisions to forgo global for local brands elicit stronger regret, lower satisfaction, and higher brand switching than regrettable purchases of global (vs. local) brands for consumers with a global brand superiority schema for the category; the inverse holds for consumers with a local brand superiority schema. Studies 2 and 3 replicate the effect and show that it is mediated by perceived decision justifiability and moderated by global identity. Study 4 further validates the observed effect using a real brand choice task in a category with a local brand–dominated schema. The findings reveal the postpurchase consequences of global/local brand choices and provide concrete advice for global/local branding strategies.